2021
DOI: 10.1111/pin.13107
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of bone – Analysis of 213 cases involving extra‐craniofacial bones

Abstract: We elucidated clinicopathological characteristics of giant cell tumor of bone (GCTB) in Japan, and significant clinicopathological factors for predicting local recurrence. Clinicopathological profiles of 213 patients with GCTB (100 male, 113 female) involving extra‐craniofacial bones were retrieved. Pathological slides obtained at the initial surgery were reviewed. Fourteen pathological and five clinical features were statistically analyzed to disclose prognostic significance. Patient age ranged from 12–80 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Several studies investigated the pathological grade of GCTB as a potential risk factor for local recurrence, and it was found that there is no correlation between pathological grade and local recurrence. [35][36][37][38] The same was found in the current study, with recurrence rates associated with low-grade and high-grade lesions similar to each other (22.4% and 33.3%, respectively); it was statistically insignificant. The grade of the lesion could not be considered as a risk factor for recurrence.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies investigated the pathological grade of GCTB as a potential risk factor for local recurrence, and it was found that there is no correlation between pathological grade and local recurrence. [35][36][37][38] The same was found in the current study, with recurrence rates associated with low-grade and high-grade lesions similar to each other (22.4% and 33.3%, respectively); it was statistically insignificant. The grade of the lesion could not be considered as a risk factor for recurrence.…”
Section: Discussionsupporting
confidence: 85%
“…Several recent studies have demonstrated that the H3F3A mutation might contribute to distinguishing GCTB-related tumors from those that are giant-cell-rich [ 10 , 52 , 53 , 54 ]. However, there are differences in the frequency of H3F3A mutations found in previous reports; these mutations were identified in 69–100% of GCTB [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. One study [ 54 ] suggested that diagnosis of GCTB without the H3F3A alteration should be confirmed with considerable caution.…”
Section: Discussionmentioning
confidence: 86%
“…[1][2][3][4] Although rarely fatal, GCTB is characterized by local invasion and occasional metastasis to the lung. [5][6][7] GCTB presents in young adults between the ages of 20 and 44 years with a higher incidence in females. 4 GCTB typically develops at the junction of the metaphysis and epiphysis of long bones and more commonly in the distal femur, proximal tibia, and distal radius.…”
Section: Introductionmentioning
confidence: 99%